2008
DOI: 10.1016/j.msea.2007.08.093
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the strength of f.c.c. and b.c.c. sub-micrometer pillars: Compression experiments and dislocation dynamics simulations

Abstract: We compare mechanical strength of f.c.c. gold and b.c.c. molybdenum single crystal pillars of sub-micrometer diameter in uniaxial compression tests. Both crystals show an increase of flow stress with decreasing diameter, but the change is more pronounced in Au than in Mo. The ratio between the observed maximum flow stress and the theoretical strength is much larger in Au pillars than in Mo pillars. Dislocation dynamics simulations also reveal different dislocation behavior in these two metals. While in a f.c.c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
86
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(93 citation statements)
references
References 30 publications
5
86
0
1
Order By: Relevance
“…2e) with a lot of quenched-in dislocations as 'fossil record' of the HSR explosive dislocation self-multiplications. Figure 3b where discrete strain bursts are also noticeable, consistent with previous reports on similar-sized Mo pillars by Greer et al 3,13,14 and Arzt et al 6,16 But due to their larger sizes, mechanical annealing should be less obvious; or rather, the effect of mechanical annealing is counterbalanced by dislocation creation inside by more traditional means (for example, Frank-Read sources).…”
Section: Mechanical Annealing In Mosupporting
confidence: 89%
See 2 more Smart Citations
“…2e) with a lot of quenched-in dislocations as 'fossil record' of the HSR explosive dislocation self-multiplications. Figure 3b where discrete strain bursts are also noticeable, consistent with previous reports on similar-sized Mo pillars by Greer et al 3,13,14 and Arzt et al 6,16 But due to their larger sizes, mechanical annealing should be less obvious; or rather, the effect of mechanical annealing is counterbalanced by dislocation creation inside by more traditional means (for example, Frank-Read sources).…”
Section: Mechanical Annealing In Mosupporting
confidence: 89%
“…In contrast, in Mo pillars, it has been shown that dislocation tangles are retained even after extensive plastic deformation 23 . This has been rationalized by MD simulations of Mo pillars as due to dislocation self-multiplication at higher stresses ( > 5.5 GPa in D = 36 nm pillar), arising from the cross-kinks generated along the screw dislocations that have non-coplanar core structure 5,14 . Many in the community believe that mechanical annealing is not possible for BCC metals regardless of sample size.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…However, image forces arising from the dislocation's interaction with the free surface have been shown to be influential on cross-slip in previous atomistic and dislocation dynamics simulations [8,9]. In this work, we employ 3D dislocation dynamics to determine the effects of these image stresses on the mechanisms which allow an incipient dislocation loop nucleated from the surface of a void to evolve into a PDL.…”
mentioning
confidence: 99%
“…[2,11] In addition, almost all previous studies of the size dependence of m of BCC metals used polycrystalline materials except the one by Schneider et al [14] They found that submicron-sized single crystal Mo pillars exhibited strain-rate sensitivity similar to their bulk counterpart. Moreover, compared with the widely studied size-strengthening effect and its underlying mechanism of single crystal BCC metals, [5,6,[14][15][16][17][18][19][20][21] much less work have been carried out on m. Recently, we demonstrated through molecular dynamics simulation [19] that very high applied stresses can diminish the velocity difference between screw and edge dislocations in single crystal Mo. As a consequence, BCC Mo behaves more like an FCC metal.…”
mentioning
confidence: 99%